A new species of treefrog (Anura: Hylidae: Litoria) from the Huon Peninsula, Papua New Guinea - Richards, Stephen J. (Zootaxa, 2005)
Litoria singadanae sp. nov. is described from lower montane rainforest on the Huon Peninsula, Papua New Guinea. It is a moderately small green frog (two males 29.0–29.1 mm, a female 34.6 mm SV) with long limbs (TL/SV 0.55–0.60), extensively webbed fingers, and a large and prominent tympanum. The new species is unique among Australopapuan hylid frogs in possessing a transparent tympanic membrane. It is known only from the type locality at an altitude of 1280 m asl.